Epidemiology of Frequent/Urgent Urination in Older Adults in China: A Multicenter, Cross-Sectional Study - Zhang, Yiwen; Wang, Xiao-Dan; Song, Yehua; Peng, Ruiqiang; Tang, Ting; Li, Miaoduan; Yu, Zhenzhen; Ji, Yong; Niu, Jianping (Frontiers in Public Health, 2021)
Background: Frequent/urgent urination is an event of multifactorial origin where involuntary leakage of urine occurs. Epidemiological study of this condition is of high importance due to its negative impact on the psychological, physical, and social well-being of the victims. Objective: This cross-sectional study aimed to investigate the prevalence of frequent/urgent urination in older adults in China. Method: In this study, a face-to-face questionnaire survey was conducted between April 2019 and August 2019 among 4,796 older adult populations in the communities of Tianjin jizhou and Xiamen jimei of China. Descriptive analysis, univariate regression, and all statistics were conducted in IBM SPSS v22. The count data were analyzed by chi-square test. P < 0.05 was considered statistically significant. Results: In the total investigated population, the prevalence of frequent or urgent urination was found in 1,164 patients (24.3%) where 31.7% (664/2,097) were male patients and 18.7% (500/2,699) were female patients, having a male-to-female ratio of 1.7:1. The prevalence was higher in the 70- to 84-year-old group (men: 33.3–34.8%, women 19.5–20.8%), whereas it was relatively low in the 65- to 69-year-old group and in older adults over 85 years of age (men 28.8, 30.3%, women 16.7, 18.5%, respectively). In terms of the course of the disease, among the population aged 65 years and above, 17.3% men and 9.9% women had frequent urination/urgency lasting for 1–4 years; 5–9 years in about 4.5% population (7.4% men and 4.2% women); 10–19 years in 4.9% men and 2.3% women; and more than 20 years duration in 1.6% men and 1.9% women. On the severity scale, mild frequent/urgent urination was observed in 24.6% of men and 15.4% women of Chinese older adults. Moderate cases were observed in 6.3% of men and 2.9% of women, whereas severe cases were found in 0.8% men and 0.2% women. Benign prostatic hyperplasia (BPH)/hypertrophy was the main risk factor for frequent/urgent urination in Chinese older adult men (P < 0.001). Obesity, hypertension, diabetes, heart disease, anxiety, depression, constipation, and brain injury were the other risk factors for frequent/urgent urination in Chinese older adult men and women. The results of this survey showed that smoking or drinking habits did not increase the prevalence of frequent/urgent urination in Chinese older adults. Conclusions: According to the results of this survey, the prevalence rate of frequent/urgent urination is high, and the course of the disease is long in Chinese older adults. BPH and depression, anxiety, and age-related chronic diseases increase the risk of frequent/urgent urination in Chinese older adults.